PENERAPAN MODEL PEMBELAJARAN SELF DIRECTED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN SOSIOLOGI SMA NEGERI 6 KUPANG - Damianus Firno (Prosiding Ilmu Pendidikan dan Keguruan, 2023)
This research aims to determine the application of the Self-Directed Learning (SDL) Learning Model to improve student learning outcomes in sociology lessons at SMA Negeri 6 Kupang. The aim of this research is to determine whether the Self-Directed Learning learning model can improve student learning outcomes in sociology lessons at SMA Negeri 6 Kupang. This research is Classroom Action Research (PTK). The subjects in this research were students in class This research was conducted in two cycles. Where in each cycle 3 meetings are held and at the end of the meeting an evaluation or final test is held in implementing the action. The data analysis technique used in this research uses qualitative and quantitative data analysis. The data collection techniques used in this research used observation sheets, tests and documentation. The research results show that implementing learning by applying the Self-Directed Learning (SDL) learning model in sociology subjects can improve student learning outcomes. This is demonstrated by increasing student learning outcomes in each cycle. In the pre-cycle the total student score reached 2365 with an average of 67.57, increasing to 2685 in the first cycle with an average of 76.71, while in the second cycle it increased to 2870 with an average of 82.85.